THERAPEUTIC DIFFICULTIES IN ACHIEVEMENT OF OPTIMAL ROOT COVERAGE AND AESTHETIC IN CLASS III GINGIVAL RECESSION. - Christina Popova; Antoaneta Mlachkova; Velichka Dosseva-Panova (Peytchinski Publishing, 2013)
The width of the attached gingiva is defined as a distance between the depth of the gingival sulcus or gingival/periodontal pocket to the mucogingival junction. Authors suggest that a minimal amount of attached gingiva is necessary to ensure the gingival health. When the buccal bone plate and gingival tissues are thin and the position of the tooth is too vestibular gingival margin often displaces apically, and gingival recession develops. In the presence of gingival recession and reduced vestibular depth oral hygiene procedures are embarrassed.The definition of class III gingival recession is marginal lack of tissue extended to/or beyond the mucogingival junction with bone and soft tissue loss interdentally or malpositioning of the tooth.Prognosis for class III and IV gingival recession is that only partial coverage can be expected after root coverage procedures - FGG (free gingival graft) or connective tissue graft (CTG). Adjunctive surgical techniques would be helpful to achieve better aesthetic outcomes.